Hubungan Pola Pemberian Makan dengan Kejadian Stunting pada Balita Usia 24-59 Bulan di Wilayah Kerja Puskesmas Mangoli Kepulauan Sula - Rahma Tunny (PPNI UNIMMAN, 2024)
Based on the results of the 2022 Indonesian Nutrition Status (SSGI) survey by the Ministry of Health, the prevalence of stunting among children under five in Maluku Province reached 26.1%. This figure puts Maluku province in the 13th place nationally. It was recorded that Maluku province cut the number of stunted children under five by 2.6 points from the previous year. In SSGI 2021, the prevalence of stunting in Maluku reached 28.7%, but this figure is still relatively high because it exceeds the threshold set by WHO of 20%. The purpose of this study is: to determine the relationship between feeding patterns and the incidence of stunting in toddlers in the working area of the Mangoli Health Center, Sula Islands. This study is an analytical observational research using a cross sectional approach. The results of the chi-square test showed that there was a meaningful relationship between feeding patterns, namely the amount of food given to toddlers with a p value = 0.002. because the p value < 0.005 thus H0 is rejected and Ha is accepted, so there is a meaningful relationship between the provision of food to toddlers and the incidence of stunting in toddlers in the working area of the Mangoli Health Center in the Sula Islands Mangoli Health Center.